Autobiografia, história e memória em À Mão Esquerda, de Fausto Wolff - Silva, Paulo Alex Souza Melo da (2010)
That dissertation analyzed the novel The left hand, by Faust Wolff, under a perpective that detach the varied content wich is formed. We take with base the concepts of memory and history, because the speeches of many narrators-characters are born, primordially, from the remomeration of the people. Related in that, the novel focus of a critic and ironic way, the social-politic from Brasil and from world, we will see some teams and aspects brought by that inverted, as the process of it conduction. We analyzed also the novel metalinguistic content, read it like the history of construction of novel. Like it is recurrent in author s literature, the novel has stronger autobiographic inclination, motive that make us to begin that work by analyze of that question